Implementasi Kebijakan Kepala Madrasah Tentang Kewajiban membaca Al Quran di Min 6 Bandar Lampung - susanti (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2026)
This research aims to see the implementation of madrasa heads regarding the obligation to read the Koran before starting teaching and learning activities. The research uses descriptive qualitative methods. Data collection tools use observation and interviews. Based on the research results, it was concluded that 1) The supporting factors for the implementation of the madrasa head's policy towards reading the Al-Qur'an were (1) A clear aim to improve the quality of education, (2) Students also really welcomed this policy, (3) Teachers played an active role in this activity. Meanwhile, the inhibiting factors for the madrasah head's policy towards reading the Al-Qur'an are (1) reading it together, so teachers don't understand who haven't memorized it; (2) competence of teachers who haven't memorized juz'amma; 2) The implementation process for reading the Al-Qur'an in MIS Nurul Hidayah Way Sulan, South Lampung Regency uses two methods, the iqro method, namely a method that directly emphasizes reading the letters of the Al-Qur'an. And the Takrir Method is a method of repeating memorization or memorizing memorization that has been memorized/has been memorized to the teacher. Teaching of reading the Al-Qur'an is carried out in the classroom and guided by the class teacher. The time allocated for teaching activities to read the Koran is 15 minutes before the teaching and learning process. Using the habituation aspect.